PWE-187 The helicobacter eradication aspirin trial (Heat): a large simple randomised controlled trial using novel methodology in primary care. (22nd June 2015) - Dumbleton, JS; Avery, A; Coupland, C; Hobbs, FDR; Kendrick, D; Moore, MV; Morris, C; Rubin, GP; Smith, MD; Hawkey, CJ
Abstract : Introduction: Clinical trials measuring the effect of an intervention on clinical outcomes are more influential than those investigating surrogate measures but are costly. We developed methods to reduce costs substantially by using existing data in primary and secondary care systems, to ask whether Helicobacter pylori eradication would reduce the incidence of hospitalisation for ulcer bleeding in aspirin users. Method: The Helicobacter Eradication Aspirin Trial (HEAT) is a HTA-funded, CRN-supported, double-blind placebo controlled randomised trial of the effects of H. pylori eradication on subsequent ulcer bleeding in infected individuals taking aspirin daily, conducted in practices across the whole of England, Wales and Northern Ireland. A bespoke web-based trial management system developed for the trial (and housed within the secure NHS N3 Data Network) communicates directly with the HEAT Toolkit software downloaded at participating practices, which issues MIQUEST queries searching entry criteria (≥60 years, on chronic aspirin ≤325mg daily, not on anti-ulcer therapy or non-steroidal anti-inflammatory drugs) for GP review of eligibility. Trial participation is invited using a highly secure automated on-line mail management system that ensures patients receive an invitation within 48 h. Interested patients are seen once for consent and breath testing. Those with a positive test are randomised to eradication treatment (lansoprazole, clarithromycin, metronidazole) or placebo with drug sent by post. Events are tracked by upload of accumulating information in the GP database, patient contact, review of national Hospital Episode Statistics and ONS data. Results: HEAT is the largest CRN CTIMP trial, with 105, 276 invitation letters sent from 772 practices, 20, 509 volunteers, and 2, 847 H. pylori positive patients randomised to active or placebo treatment after 2.5 years of recruitment. 178 practices have performed their first follow-up MIQUEST search to identify 21 potential endpoints to date. Conclusion: HEAT is important medically, because aspirin is so widely used, and methodologically, as a successful trial would show that large-scale studies of important clinical outcomes can be conducted at a fraction of the cost of those conducted by industry, which in turn will help to ensure that trials of primarily medical rather than commercial interest can be conducted successfully in the UK. Disclosure of interest: None Declared.